Physiological and metabolomic analyses reveal the mechanism by which exogenous spermine improves drought resistance in alfalfa leaves (Medicago sativa L.) - Wang, Wenjuan; Kang, Wenjuan; Shi, Shangli; Liu, Linbo (Frontiers in Plant Science, 2024)
Alfalfa (Medicago sativa L.) is a globally important legume crop with high nutritional and ecological value. Drought poses a serious threat to alfalfa acreage and yields. Spermine (Spm) has been shown to protect plants from drought damage. The aim of this study was to clarify the mechanism of exogenous Spm to improve drought resistance of alfalfa. In this study, we root applied 0.1, 0.5, and 1 mM Spm to Gannong No. 3 (G3) alfalfa under drought stress. The results showed that exogenous Spm increased chlorophyll content, chlorophyll fluorescence parameters and gas exchange parameters, enhanced antioxidant enzymes activity, improved ascorbic acid-glutathione (AsA-GSH) cycle, increased osmoregulatory substances content, reduced hydrogen peroxide and superoxide anion levels, and inhibited malondialdehyde accumulation in alfalfa under drought stress, thereby increasing plant height and leaf relative water content and enhancing drought tolerance of alfalfa. The redundancy analysis of the above physiological indicators showed that the addition of the optimal Spm to improve drought tolerance of alfalfa under drought stress was mainly achieved by increasing catalase activity and improving the ASA-GSH cycle. In addition, metabolomics analysis revealed that exogenous Spm increased the content of oxobutanedioic acid, citric acid, fumaric acid and malic acid to enhance the tricarboxylic acid cycle. Meanwhile, exogenous Spm increased endogenous Spm and proline (Pro) content to resist drought stress by enhancing Spm and Pro metabolism. Moreover, exogenous Spm increased the accumulation of the signaling substance abscisic acid.